Synthesis and Liquid-Crystalline Properties of Novel Compounds with 3-Fluoro-4-cyanophenoxy Group - MEI, ZHEN-HUA; YOU, TING-TING; BI, SAI (Asian Journal of Chemistry, 2010)
Facile and convenient synthesis of four series of novel compounds with 3-fluoro-4-cyanophenoxy group were performed by using 2-fluoro- 4-hydroxyphenyl as intermediate. The structures of these compounds were characterized by means of elemental analysis, infrared (IR), nuclear magnetic resonance (1H NMR) and mass spectra (MS). One of these compounds was found to exhibit potential liquid-crystalline properties.